1998
DOI: 10.1002/biof.5520070404
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic effects of EGF/TGFα and immunolocalization of cognate receptors in human fetal kidneys

Abstract: The involvement of epidermal growth factor (EGF) and homologous transforming growth factor (TGF) in human kidney development was studied by analyzing their effects on the regulation of DNA synthesis in organ culture and by localizing their cognate receptors. Both peptides significantly increased 3H-thymidine incorporation when added at 10-100 ng/ml, but not at 1-5 ng/ml. Furthermore, addition of an anti-EGF receptor antibody not only reduced the effect of exogenous EGF (100 ng/ml) on DNA synthesis but decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
9
0
2
Order By: Relevance
“…However, in the later investigation of the same authors, both TGF-a mRNA and protein were equally expressed in the cells of the developing collecting system, as well as in the cells of the developing nephrons (Bernardini et al 2001). Significant immunoreactivity to both factors, especially in mitotic cells, confirmed the role of those growth factors in the early growth and intense development of all metanephric structures, as previously suggested by other authors (Chailler and Briere 1998;Bernardini et al 2001). A slight decrease in their expression characterized advanced developmental stages, and was coincidental with progression in maturation of nephrons.…”
Section: The Metanephrossupporting
confidence: 83%
See 3 more Smart Citations
“…However, in the later investigation of the same authors, both TGF-a mRNA and protein were equally expressed in the cells of the developing collecting system, as well as in the cells of the developing nephrons (Bernardini et al 2001). Significant immunoreactivity to both factors, especially in mitotic cells, confirmed the role of those growth factors in the early growth and intense development of all metanephric structures, as previously suggested by other authors (Chailler and Briere 1998;Bernardini et al 2001). A slight decrease in their expression characterized advanced developmental stages, and was coincidental with progression in maturation of nephrons.…”
Section: The Metanephrossupporting
confidence: 83%
“…A slight decrease in their expression characterized advanced developmental stages, and was coincidental with progression in maturation of nephrons. Despite differences in the results, conclusions resulting from studies provided on developing human kidneys agreed on the role of both factors in supporting proliferation, and on their progressive downregulation during nephrogenesis (Bernardini et al 1996;Chailler and Briere 1998). All important developmental processes including growth of the metanephros, branching of the ureteric bud and tubulogenesis seemed to be influenced by TGF-a (Rogers et al 1992), while for EGF was additionally suggested to inhibit cell death (Coles et al 1993).…”
Section: The Metanephrosmentioning
confidence: 82%
See 2 more Smart Citations
“…The fetal ADAM17 expression could be related to its role in the shedding of EGFR ligands. TGF-␣ is of special interest, since it is abundantly expressed in the nephrogenic blastema and ureteric bud of developing rat and human kidneys (1,6). Additionally, in vitro experiments showed that TGF-␣ (23,33), and also HB-EGF and amphiregulin (25), can regulate branching tubulogenesis.…”
Section: Discussionmentioning
confidence: 97%